Study on Flow Velocity Distribution in Open Channel With Flexible Vegetation - Wang, Shiyu; Zhou, Yi; Li, Tongshu; Li, Song; Zhang, Mingwu; Han, Yu (Frontiers in Plant Science, 2021)
Ecological management of river channels is a hot topic for current sustainable development, and flow measurement of ecological river is an important part. In this paper, a flow velocity distribution model of the channel containing flexible vegetation is constructed from the vegetation riverbed theory and the bursting phenomenon to reveal the microscopic mechanism of the flow velocity distribution in the upper layer of vegetation. In the vegetation riverbed law, the effect of flexible vegetation is evaluated by the mixed length formula. The bursting phenomenon law considers the influence of the channel sidewalls on the flow, and a two-dimensional velocity model is established by introducing the concept of average turbulence structure. The mechanism of the downward shift of the maximum flow velocity point on the channel sidewall is explained. The verification of the calculated velocity profiles is carried out based on data obtained in laboratory experiments. The results show that the combination of the two models can well describe the velocity distribution of the whole channel. At the end, the phenomenon of flow velocity zoning in open channel is discussed, which provides a solution for flow measurement in ecological channel.